Size estimation of key populations and 'bridge populations' based on the network scale-up method in Ukraine - Oksana Kovtun; Volodymyr Paniotto; Yulia Sakhno; Kostyantyn Dumchev (BMC, 2024)
Abstract Introduction Correct estimation of the size of key and bridge populations is crucial for an efficient HIV/AIDS response in resource-limited settings, enabling efficient program planning and resource allocation. The hidden nature of these groups poses challenges to traditional methods, leading to the adoption of innovative approaches like the network scale-up method (NSUM). In this article we present the results of a NSUM study conducted in 2020 in Ukraine, focusing on four key populations and three bridge populations, highlighting challenges and contributions to development of the method. Methods From July to September 2020, we conducted a nationally representative survey in Ukraine via computer-assisted telephone interviews, and applied the known population method and summation method to estimate social networks sizes. Results were weighted based on individual sampling probability and adjusted for social respect and visibility factors to address potential limitations. Results Our study achieved a 20% response rate with 10,000 completed interviews. The social network size, using the known population method, was 213 people, and 125 using the summation method. Adjusting for the social respect and visibility, estimated key populations sizes were 295,857 [248,714-343,001] people who inject drugs, 152,267 [109,960-194,573] men who have sex with men, 78,385 [57,146-99,619] sex workers, and 9,963 [7,352-12,571] transgender people, detailed by age and gender. Bridge populations were estimated at 62,162 [50,445-73,879] sexual partners of people who inject drugs, 284,348 [233,113-335,583] clients of sex workers, and 13,697 [7,370-20,026] female partners of men who have sex with men. Conclusions NSUM proves reliable for estimating key populations size with appropriate corrections. It shows promise for further use in Ukraine, considering limited geographic coverage of the integrated bio-behavioral studies to use multiplier-based methods. However, the validity concerns persist for estimating bridge populations size, emphasizing the need for further method refinement and addressing implementation issues, particularly those related to data collection.